2018
DOI: 10.1007/s10461-018-2236-9
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Interventions for Adults Living with HIV/AIDS: A Systematic Review and Meta-analysis

Abstract: This meta-analysis examined the effects of mindfulness-based interventions (MBIs) on stress, psychological symptoms, and biomarkers of disease among people living with HIV/AIDS (PLWHA). Comprehensive searches identified 16 studies that met the inclusion criteria (N = 1059; M age = 42 years; 20% women). Participants had been living with HIV for an average of 8 years (range = < 1-20 years); 65% were currently on antiretroviral therapy. Between-group analyses indicated that depressive symptoms were reduced among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 60 publications
(73 reference statements)
2
30
0
Order By: Relevance
“…Mindfulness-based cognitive therapy is effective in managing and mitigating the disease symptoms and improving sleep quality in the patients (22). Scott-Sheldon et al (23), Wood (24), and Witek-Janusek et al (25) demonstrated that mindfulness is effective in enhancing the health and quality of life and reducing stress in individuals with HIV/AIDS as documented in the follow-up test after the treatment. The effectiveness of mindfulness-based cognitive therapy has also been confirmed in other studies, indicating that it improves sleep quality and reduces psychological symptoms like depression and anxiety (23).…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness-based cognitive therapy is effective in managing and mitigating the disease symptoms and improving sleep quality in the patients (22). Scott-Sheldon et al (23), Wood (24), and Witek-Janusek et al (25) demonstrated that mindfulness is effective in enhancing the health and quality of life and reducing stress in individuals with HIV/AIDS as documented in the follow-up test after the treatment. The effectiveness of mindfulness-based cognitive therapy has also been confirmed in other studies, indicating that it improves sleep quality and reduces psychological symptoms like depression and anxiety (23).…”
Section: Discussionmentioning
confidence: 99%
“…Zinn takes a modern scientific-based perspective on traditional Buddhist principles of meditation and develops a more flexible approach to reducing stress. In doing meditation, it can be done by sitting, standing, squatting, kneeling or in other positions (16). When doing meditation, it is responsible for mental states and learning to change our reactions to experiences the positive results (17,18,19,20).…”
Section: Mindfulness-based Stress Reductionmentioning
confidence: 99%
“… 4 For PLWH, stress can increase viral replication, suppress their immune response, and interfere with their adherence to antiretroviral therapy (ART). 5 , 8 …”
Section: Introductionmentioning
confidence: 99%